2017
DOI: 10.24193/cbb.2017.21.14
|View full text |Cite
|
Sign up to set email alerts
|

Hungarian adaptation and psychological correlates of Source of Enjoyment in Youth Sport Questionnaire among high school students

Abstract: Several studies have reported a decreasing tendency of engagement in physical activity during adolescence. Since previous research suggests that enjoyment could be a key predictor of sport participation, the aim of this study was to validate the Source of Enjoyment in Youth Sport Questionnaire (SEYSQ) and to investigate the relationship between sport enjoyment and different psychological correlates such as future orientation, satisfaction with life and future life aspirations. First, we conducted an explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…There were no significant differences in total SEYSQ score between the youngest grade (6 th grade; mean age=11.8; standard deviation ± 0.5 years) and oldest grade (8 th grade; mean age=13.6; standard deviation ± 0.5 years) of athletes who participated in this study. Previous studies have suggested that sport engagement and enjoyment decrease as age increases among youth athletes (McCarthy et al 2008, Berki andPiko 2017). However, the current study showed no significant difference between younger and older participants in terms of enjoyment.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…There were no significant differences in total SEYSQ score between the youngest grade (6 th grade; mean age=11.8; standard deviation ± 0.5 years) and oldest grade (8 th grade; mean age=13.6; standard deviation ± 0.5 years) of athletes who participated in this study. Previous studies have suggested that sport engagement and enjoyment decrease as age increases among youth athletes (McCarthy et al 2008, Berki andPiko 2017). However, the current study showed no significant difference between younger and older participants in terms of enjoyment.…”
Section: Discussioncontrasting
confidence: 79%
“…The Sources of Enjoyment in Youth Sport Questionnaire (SEYSQ) (Wiersma 2001) is a 28-item survey that quantifies sport enjoyment by, among other things, measuring the level of intrinsic and extrinsic motivation (Figure 1). Using the SEYSQ for data acquisition 526 adolescents, Ages 14-18, participated in a study conducted by Berki and Piko (2017). Their study"s research indicates that "there are important differences according to age and gender in the sources of sport enjoyment" (Berki and Piko 2017, p. 230).…”
Section: Introductionmentioning
confidence: 99%
“…Claims about the benefits of intrinsic aspiring and costs of extrinsic aspiring have received support across a wide variety of countries and cultures (Andronikos et al, 2021; Bradshaw et al, 2021; Unanue et al, 2014), age groups (Berki & Piko, 2017; Mackenzie et al, 2018), socioeconomic statuses (Stevens et al, 2011; Tuicomepee & Romano, 2005; Wasser, 2011), and special interest groups such as problem drinkers and prison inmates (Bradshaw et al, 2018; Kasser & Ahuvia, 2002). Yet, there have been exceptions.…”
mentioning
confidence: 99%
“…Fathers responded on a Likert scale ranging from 1 ("not important at all"), 3 ("moderately important"), to 7 ("very important"). The reliability of this instrument has been shown by previous studies, reporting Cronbach's alpha coefficients between 0.80 and 0.96 for intrinsic aspirations and 0.71 and 0.92 for extrinsic aspirations [28,[32][33][34].…”
Section: Instrumentsmentioning
confidence: 85%